Assessment of Ambient Air Quality and Air Quality Index in Golden Corridor of Gujarat, India: A Case Study of Dahej Port - Soni, Hiren B.; Patel, Jagruti (International Journal of Environment, 2018)
Clean air is the basic requirement of all living organisms. In recent times, due to population growth, urban sprawl, industrial development, and vehicular boom, the quality of air is deteriorating and being polluted. Pollutants of major public health concerns include particulate matter, carbon monoxide, ozone, nitrogen dioxide, and sulfur dioxide, which pose serious threats to human health and hygiene. In the present study, prime particulate pollutants (PM10, PM2.5), and gaseous pollutants (SO2, and NO2) were estimated at seven stations in and around Dahej Port, Gujarat, India. The obtained values of PM10, PM2.5, SO2, and NO2 in all the studied stations (seven) ranged from 67.39 to 98.75, 29.57 to 45.79, 17.76 to 22.29 and 28.29 to 32.42 mg/m3, respectively. The level of PM10 at all sampling locations, and that of PM2.5 at Station A3 (Lakhigam) were found little higher than prescribed permissible limits of CPCB standards, while SO2 and NO2levels were within the acceptable range. The Air Quality Index (AQI) score was found to be ranged from 76.50 to 97.75, which is at satisfactory level as per CPCB standards. Further, precautionary measures and management strategies to minimize the effect of particulate as well as gaseous pollutants have also been suggested for achieving its ambient levels in and around Dahej Port, Gujarat, India. International Journal of Environment Volume-6, Issue-4, Sep-Nov 2017, page: 28-41